Pengaruh Pemberian Dosis Pupuk Kandang Kambing dan NPK terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) - Putu Bijak Adhistanaya; I Gusti Bagus Udayana; Made Sri Yuliartini (Fakultas Pertanian, Universitas Warmadewa, 2025)
Increasing the productivity of Pakcoy plants which have good quality and high yields requires providing nutrients to the plants such as fertilization. Fertilizers that can be used are goat manure and NPK fertilizer. This research aims to determine the optimal dose of goat manure and NPK fertilizer to increase the growth of Pakcoy plants. This research used a factorial randomized block design consisting of two treatment factors. The first factor is goat manure (PK) which consists of four levels, namely 0; 0.5 ; 1 and 1.5 kg/polybag. The second factor is the concentration of NPK fertilizer which consists of four levels, namely 0; 1 ; 2 and 3 g/polybag. Observed variables included: Maximum plant height (cm), Number of Planting Leaves (Strands), Fresh weight of economic yield per plant (g), Total plant weight (g), Oven dry weight of Stove (g), Fresh weight of stover (g) , and oven dry weight of economic yield per plant (g). The experimental data were analyzed statistically using analysis of variance according to the design used. If the treatment has a significant or very significant effect, continue with the average value difference test using the 5% BNT test method. The results of the research showed that giving a dose of goat manure had a very significant effect (P<0.01) on the total weight of the plant and the economic fresh weight of the pak choy plant. The NPK dosing treatment had a significant effect (P<0.05) on the dry weight of the economical oven. The interaction between treatments of providing doses of goat manure and NPK had no significant effect on the growth of pakcoy plants. The highest economic fresh weight of pak choy plants was obtained in the treatment of providing goat manure at a dose of 1 kg/polybag with a fresh weight percentage of 83.36% and NPK fertilizer at a dose of 2 g/polybag with a fresh weight percentage of 85.27%.